Fatal Disseminated Cryptococcus gattii Infection in New Mexico - Walraven, Carla J.; Gerstein, Wendy; Hardison, Sarah E.; Wormley, Floyd; Lockhart, Shawn R.; Harris, Julie R.; Fothergill, Annette; Wickes, Brian; Gober-Wilcox, Julie; Massie, Larry; Ku, T. S. Neil; Firacative, Carolina; et al. (PLOS ONE, 2011)
We report a case of fatal disseminated infection with Cryptococcus gattii in a patient from New Mexico. The patient had no history of recent travel to known C. gattii-endemic areas. Multilocus sequence typing revealed that the isolate belonged to the major molecular type VGIII. Virulence studies in a mouse pulmonary model of infection demonstrated that the strain was less virulent than other C. gattii strains. This represents the first documented case of C. gattii likely acquired in New Mexico.